(3EOGQI GdeMGaX GdeGdjIs (3OQhS hJWHjbGJ eOYheI HeSGFd hJeGQjf eMdhdI hCNQi ebJQMIs - (3Hf efUhQ(B, (3ehSis ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdETgGQs, 2022)
(3eaGgje hCSGSjGJ Mhd GdGSJKeGQ aj GdeMaXI GdeGdjI, YGFO heNGWQ GdGSJKeGQ aj GdeMaXI GdeGdjI,GdeMaXI GdeGdjI GdeKdi hfXQjI GdcefaYI, hfeGPL GdQHW Hjf GdYGFO hGdeNGWQI hJbjje COGA GdeMGaX GdeGdjI, eSGFd hJWHjbGJ Mhd GNJjGQ GdeMaXI GdeGdjI(B.s
Keywords: (3GdGSJKeGQs; (3GdeMGaX GdeGdjIs